Abordaje en el servicio de emergencias de la infección por Neisseria meningitidis - Villalobos Zuñiga, Manuel (2019)
Meningoccocal disease is one of the leading causes of death in children and adults in emergency services. The presence of nonspecific symptoms as headache, fever and myalgias can cause delayed diagnosis, mainly due to a late start of antibiotics, thus producing an increasein morbidity and mortality and disabling potential among those who survived the disease, due to the long-term neurological damage. On the other hand, the presence of a petechial skin rash in a critically ill patient or with meningeal signs should remind us of acute meningoccemia, and the approach of these patients should never be delayed due to its high mortality. In the emergency room should always be considered the isolation from secretions by drops of those patients with suspected meningococcal disease or with a confirmed diagnosis, as well as adequate prophylactic antibiotic therapy must be start immediately to those who had direct contact with patient´s nasopharyngeal secretions.